If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -87 = 7 + 2(-7 + -5r) -87 = 7 + (-7 * 2 + -5r * 2) -87 = 7 + (-14 + -10r) Combine like terms: 7 + -14 = -7 -87 = -7 + -10r Solving -87 = -7 + -10r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '10r' to each side of the equation. -87 + 10r = -7 + -10r + 10r Combine like terms: -10r + 10r = 0 -87 + 10r = -7 + 0 -87 + 10r = -7 Add '87' to each side of the equation. -87 + 87 + 10r = -7 + 87 Combine like terms: -87 + 87 = 0 0 + 10r = -7 + 87 10r = -7 + 87 Combine like terms: -7 + 87 = 80 10r = 80 Divide each side by '10'. r = 8 Simplifying r = 8
| -48=-3c+9 | | 5x-3y-10=0 | | 12-3(5-1)= | | (-4.93)(-2.1)= | | .6y+1=1.4y-15 | | -126=6(-5+2n) | | 4x^2+26x+12=36 | | y+3=20 | | (39-2x)(21-2x)x=equation | | -5.79+3.11y-4.97-2.13y= | | 0.7x-12=-13.75 | | 10x+5=5(1+2x) | | 16+7r-8+7r=8r+5r | | 3(p-3)+7=32-4(2p+5) | | 4.5(x+7)=41.85 | | 34-6x=6-10x | | 4x+11=-49-6x | | (-8+3i)+(-5i)= | | 2+11x=-48+x | | X+12yi=3-6i | | (2x+1)(3-x)=0 | | 3(4x-1.5)-2x=17 | | 8*(x-2)=32 | | 9+4*x=29 | | 315=7(6m+3) | | 12-3*x=3 | | -2x-4=32 | | 7x-17=6x+7 | | (X+6)+x+2x=35 | | .333x-4=2 | | 2*(y^2)-x^2=0 | | -2(12)+12y=47 |